(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study explores the cognitive while-reading strategies used by eleventh-grade students at SMA Negeri 9 Palangka Raya in their English reading comprehension. A total of 20 students participated in the study, completing a questionnaire based on Bezci’s (1998) model of cognitive reading strategies. The results indicate that students most frequently employed strategies such as relating the text to background knowledge, guessing word meanings from context, and considering surrounding sentences to infer meaning. Less frequently used strategies included thinking aloud during reading and skipping unknown words. These findings suggest that cognitive strategies play a crucial role in enhancing reading comprehension, and that teachers should focus on promoting the use of these strategies to improve students’ reading skills. The study contributes to the understanding of reading strategies in EFL contexts and provides practical implications for English language instruction.